Pengaruh Harga dan Keragaman Produk terhadap Minat Beli Konsumen Bloods Clothing Industries Concept Store Karawang - Hermansyah, Naoval Savira; Savitri, Citra; Faddila, Syifa Pramudita (Perhimpunan Sarjana Ekonomi dan Bisnis, 2024)
This study aims to analyze the influence of price and product diversity dimensions on consumer purchase intention at Bloods Clothing Industries Concept Store Karawang. In the rapidly evolving fashion business context, Bloods Clothing Industries faces the challenge of intensifying competition in the market. The main issue under investigation is how Bloods Clothing Industries navigates the dynamics of competition and creates a strong consumer purchase intention. This research employs a quantitative approach by collecting data from consumers who visited the store during a specific period. The collected data is subjected to statistical analysis techniques, and the structural model is tested using SmartPLS 4.0 software. The research findings reveal that factors such as price and product diversity significantly influence consumer purchase intention. Price-related aspects, including affordability, price-quality alignment, price competitiveness, and price-benefit correspondence, play a crucial role in shaping purchase intention. Additionally, product diversity in terms of materials and design also has a positive impact on consumer purchase intention. The implications of this study suggest that Bloods Clothing Industries concept store Karawang should consider marketing strategies that focus on competitive pricing dimensions and diverse products appealing to consumers. A better understanding of the factors influencing purchase intention can assist companies in making informed decisions to confront competition and enhance customer loyalty.